2022
DOI: 10.1212/wnl.0000000000200383
|View full text |Cite
|
Sign up to set email alerts
|

Positive Airway Pressure and Cognitive Disorders in Adults With Obstructive Sleep Apnea

Abstract: Background and Objectives:Alzheimer’s disease (AD) and other forms of dementia represent a rising global public health crisis. As effective treatments to prevent, cure, or slow progression of dementia are unavailable, identification of treatable risk factors that increase dementia risk, such as obstructive sleep apnea (OSA), could offer promising means to modify dementia occurrence or severity. Here we systematically reviewed the impact of positive airway pressure (PAP) therapy on incidence of cognitive disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
1
16
0
1
Order By: Relevance
“…More evidence from the AD biomarker perspective suggests that cognitively intact OSA individuals have higher Aβ burden indicated by blood, CSF and imaging biomarkers compared to individuals free of OSA [ 138 , 139 ]. Moreover, adherence to positive airway pressure therapy may lower the odds of incident diagnosis of AD or MCI and slow cognitive impairment or its progression to AD [ 140 , 141 ]. Consistently, another longitudinal analysis revealed increased risk of PD in individuals with sleep apnea [ 142 , 143 ].…”
Section: Bi-directional Relationship Of Circadian Rhythm Dysregulatio...mentioning
confidence: 99%
“…More evidence from the AD biomarker perspective suggests that cognitively intact OSA individuals have higher Aβ burden indicated by blood, CSF and imaging biomarkers compared to individuals free of OSA [ 138 , 139 ]. Moreover, adherence to positive airway pressure therapy may lower the odds of incident diagnosis of AD or MCI and slow cognitive impairment or its progression to AD [ 140 , 141 ]. Consistently, another longitudinal analysis revealed increased risk of PD in individuals with sleep apnea [ 142 , 143 ].…”
Section: Bi-directional Relationship Of Circadian Rhythm Dysregulatio...mentioning
confidence: 99%
“…A review of five systematic reviews and meta-analyses concluded that treatment with CPAP improved attention/vigilance, executive dysfunction, memory, and global cognitive functioning in non-demented individuals ( 114 ). A more recent systematic review demonstrated a protective effect that treatment with CPAP has on MCI and AD incidence ( 115 ). Several studies have suggested that treating OSA using CPAP in AD patients may slow the rate of cognitive decline ( 58 , 59 , 116 ).…”
Section: The Rationale For Implementation Of Imsm In General Neurolog...mentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a common sleep related disorder with the symptoms of upper airway collapse, apnea, hypoxia and recurrent arousals, accompanied by decline in cognitive function [ 8 , 9 ]. Sleep-disordered breathing was linked to an increased risk of cognitive impairment and AD in the elderly population [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%